Zjawiska kryzysowe — geneza i wyzwania dla państwa w ujęciu Wincentego Stysia - Kowalczyk, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Wincenty Styś claimed that business fluctuations are natural consequences of economic growth in the conditions of freedom. He searched for an answer to the question of the causes of crisis phenomena in economy in order to be able to counter them effectively. In his opinion, economic fluctuations were caused by insufficient demand and barriers limiting the growth of consumption. He believed the sources of crisis lay in investment activities of entities and fluctuations on the money market, which accompany such activities. Styś supported active state, which should counteract cyclical fluctuations of economy and prevent their negative outcomes. He suggested increasing the share of larger layers of the population in the generated income, in order to increase the level of demand. Additionally, he recommended dissemination of property and linking its amount with work. He claimed that the state should stabilize the economy using the tools of fiscal and monetary policies. Public investments, in his eyes, allowed for increasing employment and income of the population, whereas planning, if part of the market system, effectively protected economy from fluctuations.
Keywords: Styś, Wincenty (1903-1960); rola państwa w gospodarce; historyczna szkoła ekonomii; cykle koniunkturalne